The Effect of Principal Supervision and Teacher Motivation on Student Learning Achievement: Pengaruh Supervisi Kepala Sekolah dan Motivasi Guru terhadap Prestasi Belajar Siswa - Khusni, Khusni; Rahman, Novianti Azizah; Murtadoilah, Hendi; Nurfirdaus, Nunu (Journal of Society and Development, 2025)
Student academic achievement is influenced by various factors, including the effectiveness of principal supervision and teacher motivation in the learning process. This study aims to analyze the influence of principal supervision as an instructional leadership function and teacher motivation on student academic achievement. A quantitative approach with a survey design was employed. The sample consisted of 44 respondents, including grade IV, V, and VI teachers as well as grade V students from several elementary schools in Cirebon Regency. Data were collected through observation, interviews, document analysis, and questionnaires, and were statistically analyzed using the product-moment correlation formula. The results indicate that: (1) principal supervision has a positive effect on student academic achievement, contributing 55.4%; (2) teacher motivation also positively affects student achievement, contributing 53.8%; and (3) there is a significant simultaneous effect of both principal supervision and teacher motivation on student academic achievement, as indicated by a significance value of 0.000 (p < 0.05), leading to the rejection of the null hypothesis. This study provides empirical evidence highlighting the importance of principals’ supervisory roles and the enhancement of teacher motivation in improving student learning outcomes. The findings suggest the need for leadership training programs for principals and professional development initiatives for teachers as key strategies to improve the quality of education at the elementary school level.